2013
DOI: 10.2478/v10212-011-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management and Organizational Culture: An Exploratory Study

Abstract: Purpose of the article Knowledge has been considered as the strategic assets and become the source of competitive advantage in organizations. Knowledge management thus receives the extraordinary attention from the top management. Many organizational factors have influences on knowledge management practices. This paper attempts to explore the empirical relationship between knowledge management and organizational culture in the specific situation of China’s commercial banking industry. Methodology/methods The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…The results finding confirmed that organization culture effects negatively and significant on the health service innovation, means that when the organization is decrease one point, it may be caused the reduce the health service innovation. This finding is also supported by many researchers [6], [43], [48], [59]- [63].…”
Section: A Organizational Culture Effects On Health Service Innovationsupporting
confidence: 80%
See 1 more Smart Citation
“…The results finding confirmed that organization culture effects negatively and significant on the health service innovation, means that when the organization is decrease one point, it may be caused the reduce the health service innovation. This finding is also supported by many researchers [6], [43], [48], [59]- [63].…”
Section: A Organizational Culture Effects On Health Service Innovationsupporting
confidence: 80%
“…Knowledge management refers to learning organization should become a central element of achievement to get the innovative production [67]. In profit organization, many researchers have found that knowledge management and organizational culture have relationship in developing the organization service innovation [26], [63]. In this study, we have proposed the hypothesis that knowledge management will have an effect on the health service innovation, and according to the regression estimate based on the SEM analysis, we found the result of path coefficient was β = .556.…”
Section: B Knowledge Management On Health Service Innovation Andmentioning
confidence: 99%
“…Organisational culture has been identified as both a major obstacle and an empowering factor in knowledge management. Research has focused mainly on cultural barriers to knowledge management and aspects of the cultural environment that nurture it (Chang and Lin 2015;Holste and Fields 2010;Li et al 2013). However, it is also the case that knowledge management can have a great impact on, rather being influenced by, organisational culture.…”
Section: Organisational Culturementioning
confidence: 99%
“…To this end, knowledge management has evolved from an interest in information management, through an emphasis on knowledge-sharing and more recently to ways of understanding the impact of knowledge management on organisations and their culture (Holste and Fields 2010). Attempts to change organisational culture are intended to lead to continuous improvement, with a view to increasing competitive advantage (Chang and Lin 2015;Li et al 2013). In this content, knowledge management is a means to organisational learning (Allameh et al 2011).The case for knowledge management is often made a strategic level.…”
mentioning
confidence: 99%
“…Ultimately, most managers realize that a productive workforce and climate will provide a global, sustainable and competitive advantage for a learning organization. On the same lines, KM has attracted individual responsibility of employees' (Li et al, 2013). Recently, researchers have paid interests in this arena because of its acute role displayed in the competitive business world as well as OR (Linnenluecke, 2017).…”
Section: Introductionmentioning
confidence: 99%